Hubungan Pengetahuan dan Dukungan Keluarga dengan Imunisasi Tetatus Toxoid pada Ibu Hamil di Wilayah Kerja Pukesmas Krueng Barona Jaya Kabupaten Aceh Besar - Fauziah Fauziah; Muhammad Daud; Puput Novia (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
Tetanus toxoid immunization for pregnant women is a useful preventive action, so mothers can be protected from tetanus and protect their babies from neonatal tetanus. This type of immunization given to preganant women is the TTI to TT2 immunization. Low immunization coverage among pregnant women is caused by various factors, including knowledge and family support. This study aims to explore the relationship between knowledge and family support and tetanus toxoid immunization among pregenant women in Krueng Barona Jaya Haalth Center, Aceh Besar. This research employed an analytical approach with a cross-sectional design. The population consisted of 226 pregnant women was chosen by using a random sampling technique. This research was conducted from april 14th to 30th, 2025. The data was analyzed using unibivariate and bivariate mothods with the chis-square test. The research result showed that out of 73 respondents, the manjority of pregnant women hand icomplete tetanus toxoid immunization (44 respondents, 60.3%), and the rest had poor knowledge about tetanus toxoid immunization (28 respondens, 38.3%). Additionally, the result also revealed that family support for tetanus toxoid immunization was low (41 respondents, 56.2%). The chi-square test result showe a p-value of knowledge was 0,001 and for family support was 0.005, indicating a relationship between knowledgeand family support with tetanus toxoid immunization. These findings show a significant relationship between knowledge and family women. This study recommends that Kruen Barona Jaya Health Center Improve is healthcare services,particularly tetanus toxoid immunization services for pregnant women.